Curating African Identity in Postcolonial & Digital Spaces - Lipshitz, Danya (University of the Witwatersrand, Johannesburg, 2024)
This research interrogates the notion of "Authenticity" in the context of African art, both within the continent and the diaspora, particularly in digital platforms. Using Artspace.Africa—a reimagined version of the exhibition Africa Remix: Contemporary Art of a Continent—as a focal point, the study explores the complexities of African identity, spirituality, and spatial representation. I adapt Simon Njami's original thematic divisions— Identity & History, Body & Soul, and City & Land—while integrating Henri Lefebvre's layered concept of 'space,' involving physical, planned, and lived spaces. This curatorial approach aims to challenge monolithic perceptions of Africa, illuminating its diversity through an exploration of different types of space as theorised by Lefebvre. The methodology is qualitative, using my own curation as the primary lens for investigation. I consider the implications of digital platforms on the perceived "Authenticity" of artworks and the transformative role of the digital realm in archiving and exhibiting African art. The study also acknowledges its limitations, particularly concerning the digital divide and the limited access to the internet within a South African context. This research aims to contribute to a deeper, more nuanced understanding of African art and its multi-dimensional representations in the digital age.
A research report Submitted in fulfillment of the requirements for a Master of Arts , In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: Curating African Identity; UCTD; Digital Spaces; Postcolonial; SDG-9: Industry, innovation and infrastructure